The Effect of Job Rotation, Work Stress, and Job Satisfaction on Employee Performance: A Case Study at a State-Owned Bank in Indonesia - B. Andreas Mada; M. Raihan Ramiz (Lembaga Bale Literasi, 2026)
This research aims to analyze the influence of Job Rotation, Job Stress and Job Satisfaction on Employee Performance. The population in this study were employees at PT Bank Tabungan Negara Tbk Blok M Branch, Jakarta. The number of samples in this research was 100 employees of PT Bank Tabungan Negara Tbk Blok M Branch, Jakarta. The sampling method uses purposive sampling. This research uses SPSS version 27 software. Partially, the two variables, namely job rotation and job satisfaction, have a significant effect on employee performance, indicating that every increase in the value of job rotation and job satisfaction will affect the employee's performance value. The other variable, namely work stress, does not affect employee performance, which means that every increase in the work stress value will not increase or decrease the employee's performance value. However, even though work stress has no influence in determining employee performance, it is important to maintain and pay close attention to it. Simultaneously, these three variables together have a significant influence on employee performance, indicating that every increase in the value of these three variables will increase the employee's performance value.